Me on the map - Sweeney, Joan, 1930-2017.; Leng, Qin (New York : Dragonfly Books, 2018)
A child describes how her room, her house, her town, her state, and her country become part of a map of her world.
1.8
K-3
K-3
Keywords: Maps -- Juvenile literature; Maps; Maps; Picture books